Around the World in 18 Elements. By David Scott. Issue 41 (6th October 2014) - Grohmann, Andreas
<x xml:space="preserve">Abstract</x> Royal Society of Chemistry, Cambridge, 2014. 235 pp., softcover, £ 19.99.—ISBN 978‐1849738040<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>